STUDENTS’ PERCEPTION ABOUT CLINICAL LEARNING ENVIRONMENT IN THE PRIMARY, SECONDARY AND TERTIARY MEDICAL FACILITIES - Dian Puspita Dewi; Gandes Retno Rahayu; Tri Nur Kristina (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2018)
Background: Learning environment is an important factor in learning process and can affect students' competence and work-readiness. Learning environment is not only about physical facilities but also social and psychological condition. The complexity of clinical learning environments pose challenges and problems that may affect students learning process so it is necessary to monitoring and evaluating students learning environments. This study aims to assess students' perception of their learning environment and the effect of primary, secondary and tertiary health care services utilization as clinical learning environments.Method: This study was conducted with a cross sectional study design. The subjects were 36 students of obstetrics and gynecology department. Data obtained from learning environment questionnaires in tertiary, secondary and primary health care services. A non-parametric test was applied to compared learning environment score in each health care level.Results: Students perception of their learning environment between tertiary and secondary as well as tertiary and primary health care services were significantly different. Students stated advantages and disadvantages of each learning environment that can affect their competence level. Conclusion: Students have a good perception of the their learning environment. There was significant difference between tertiary and two other health care services.